Structural, morphological, and electrochemical properties of MXene/MoS2-based supercapacitor - Mohd Abid, Mohd Asyadi 'Azam; Munawar, Rose Farahiyan; Kosnan, Muhammad Akmal; Takasaki, Akito (Penerbit Universiti Malaysia Perlis, 2024)
Two-dimensional (2D) materials, inclusive of molybdenum disulfide (MoS2), are auspicious due to their structure providing absorption sites and shorter diffusion paths. However, their sheet restacking affects the functional properties, resulting in the device’s low efficiency. A strategy is proposed to combine MoS2 with MXene material. X-ray Diffraction data revealed peaks at d-spacings of 6.07, 2.72, 2.49, 2.27, 1.82, and 1.53 Å. X-ray photoelectron spectroscopy shows prominent peaks for C 1s and Ti 2p, with no signal for Al detected in the pristine Ti3C2 MXene. This indicates successful etching of the Al layer. Electron Microscopes were used to confirm the samples’ morphology and showed that the hybrid sample has a layered flake-like structure with a small sphere attached to the surface. While the HR-TEM confirmed the layered structure of Ti3C2 after exfoliation from Ti3AlC2, consistent with prior studies. Prior, the electrochemical performances of the MXene/MoS2 supercapacitor in 6M KOH aqueous electrolyte were examined through cyclic voltammetry and galvanostatic charge–discharge. The highest specific capacitance reached was 139.71 Fg-1, attributed to heterostructures of an equally distributed MoS2 and MXene. Furthermore, the device retained about 83% of its initial capacitance after 10,000 cycles of cyclic stability testing. The results demonstrated that the MXene material improved the capacitive performance of MoS2, and conversely. Further enhancements can be expected as a result of a major omission in electrode synthesis, particularly the importance of delamination in MXene preparation.